Penggunaan Metode Integratif dalam Pembelajaran Kemampuan Membaca Bahasa Jerman - Nur Reski; Misnawaty Usman (Phonologie : Journal of Language and Literature, 2022)
Abstract. The purpose of this study was to obtain data and information regarding the effectiveness of using integrative method in learning to read and understand German for class XI students of SMA Negeri 11 Makassar. This type of research was Pre-Experimental Design (one group pre-test post-test design). The population of this research was the students of class XI SMA Negeri 11 Makassar which consists of 3 classes. The sample was 1 class, namely class XI IPS 3 which consistsed of 34 students. The sample of this study was selected using purposive sampling. Data were analyzed by t-test. The results of data analysis showed that the value of tcount 54.41 ttable 1,998 at a significant level of 0.05. The results of this study indicate that the use of integrative method in learning to read and understand German in Class XI SMAN 11 Makassar was very effective.Keywords: Effectiveness, Integrative Method, Reading Understand